Does the Microfinance Reduce Poverty in India? : Propensity Score Matching based on a National-level Household Data /: Propensity Score Matching based on a National-level Household Data. (September 2006) - Arun, Thankom; Imai, Katsushi S; Sinha, Frances
No abstract available